An Error Analysis of Prepositional of Collocation in Thesis of English Education Department IAIN Bukittinggi - Anggraini, Windy; Reflinda, Reflinda; Melani, Melyann; Irwandi, Irwandi (ALSYS, 2023)
This study is a quantitative descriptive study aimed at describing the types of prepositional collocations found in 30 samples along with their frequency of occurrence. The sample for this study was taken by collecting 294 theses for alumni majoring in English and then 30 theses were taken randomly. The results showed that the type of collocation presented was grammatical collocation in prepositions. The grammatical types of prepositions are adjective total is 2658. The most frequent collocations are collocations with 238 (8.95%) The total collocation error in the preposition is 1,32%. Based on the research result, the researcher found that there are 3 types of collocation error in preposition. The first types are ommision, the second types are addition and the last types are missinformation, the researcher did not find the missordering types for collocation error in preposition.